Bright light therapy as a method of supportive treatment of depression in pregnancy, puerperium and other selected psychiatric diseases. - Paulina Gdańska; Iwona Kiersnowska; Joanna Baranowska; Marta Kotomska; Piotr Węgrzyn (Kazimierz Wielki University, 2019)
The paper presents the role of phototherapy in treatment of depression in pregnancy, puerperium and other selected psychiatric diseases. Bright light therapy can be used as an independent form of treatment or as a method supplementing pharmacotherapy. The treatment is based on the use of light that mimics natural sunlight during light therapy sessions. Phototherapy is an optimal solution when treating depressive moods, especially seasonal depression associated with deficiency of sunlight. In the autumn-winter season the production of serotonin responsible for the proper functioning of the nervous system and general well-being, is physiologically reduced. Therefore, the use of light seems to be a reasonable treatment for depressive moods. Light therapy was also adopted in the treatment of schizophrenia, post-stroke depression and eating disorders. This method is characterized by high safety profile, a small number of mild side effects and a simple treatment scheme. In view of the above, it is a convenient method to be used in clinical conditions.